Risk Factors, Prognosis and Rapid Screening in Patients with Acute Aortic Dissection Complicated with Type 2 Diabetes - HUANG Lujie, ZHANG Xiaoying, YU Shasha (Zhongguo quanke yixue)
Background The incidence of acute aortic dissection with type 2 diabetes is on the rise; however, relatively little research has been done on its risk factors and prognosis. Therefore, actively seeking a simple and effective diagnostic tool has become the focus of research. Objective To analyze the risk factors, prognosis and rapid screening of AAD patients with type 2 diabetes. Methods A total of 168 patients with AAD admitted to Ningbo Medical Center Li Huili Hospital from January 2016 to October 2022 were selected as the study objects, and the patients were initially screened and triaged using the aortic dissection detection risk score (ADD-RS) table. Aortic CTA was selected as the "gold standard" for the diagnosis of AAD, and the diagnostic results of aortic CTA were compared with the preliminary screening results of ADD-RS. The general data of the diabetic group and the non-diabetic group were compared, and the risk factors of type 2 diabetes in AAD patients were analyzed by multivariate Logistic regression analysis. The short-term prognosis and pain score of the two groups were compared. The factors influencing the short-term prognosis of AAD patients were analyzed by Cox regression analysis, and the predictive value of ADD-RS was analyzed by ROC curve. Results 59 patients with AAD combined with type 2 diabetes (diabetes group) and 109 patients with AAD combined with non-diabetes (non-diabetes group) were screened by ADD-RS table. Multivariate Logistic regression analysis showed that increased age (OR=1.088, 95%CI=1.042-1.136, P<0.001), BMI≥25 kg/m2 (OR=2.000, 95%CI=1.421-2.834, P<0.001), coronary heart disease (OR=7.654, 95%CI=1.850-31.677, P=0.005), hyperlipidemia (OR=4.948, 95%CI=1.384-17.681, P=0.014), and LVEF (OR=1.199, 95%CI=1.109-1.297, P<0.001) were risk factors for AAD combined with type 2 diabetes. There was no statistically significant difference in pain score between AAD patients with or without diabetes mellitus (P>0.05), and the 30-day mortality of the two groups was 3.39% and 3.67%, respectively, with no statistically significant difference between the two groups (P>0.05). Cox regression analysis showed that hypertension was not an independent factor affecting the short-term prognosis of patients with acute aortic dissection (HR=0.673, 95%CI=0.094-4.791, P>0.05). The ADD-RS score of the diabetic group was 1 (1), significantly higher than that of the AAD patients in the non-diabetic group 1 (2) (Z=-4.640, P<0.001). The high risk and moderate risk in diabetic group were higher than those in non-diabetic group (Z=2.309, P=0.021). The maximum area under ROC curve is 0.706 (95%CI=0.634-0.779) . Conclusion Risk factors for AAD patients with type 2 diabetes include age, BMI≥25 kg/m2, coronary heart disease, hyperlipidemia, and LVEF. Moreover, ADD-RS score has high clinical value in the risk assessment of AAD patients with type 2 diabetes.